Religious Morality as a Pillar of Social Stability in Facing the Modern Ethical Crisis (Case Study of Ma'had Ibnu Zubair Padang) - Amanah, Tegu Reski; Zulfikar, Kartolo; Kustati, Martin; Sepriyanti, Nana (Jurnal Penelitian Pendidikan Islam, 2024)
Social transitions and changes in the modern era include a number of aspects and dynamics that influence the way a person or society interacts. Morals are a set of principles or values ​​that govern human behavior and decisions, helping determine what is considered good or bad, right or wrong in the context of everyday life. Morality includes ethical norms and standards of behavior that develop in a society or individual. Social stability refers to balance in society, social stability covers various aspects, including security, justice, social cohesion, and prosperity. The research method used is qualitative from observation data which is demonstrated by the process of recording student behavior patterns as subjects through exploration and analysis related to statements, reports, from sources, the results of the research contained will be analyzed based on several relevant theories and literature. The results of this research explain that Mahad Ibnu Zubair Padang is an educational institution that integrates Islamic values ​​in the form of a religious spirit, integrity, empathy and caring, as well as moral independence in order to form a generation that is Islamic, intellectual and has morality in ensuring social stability in the modern era.